A (re)construção das políticas municipais de educação em tempos de reforma do Estado: um novo horizonte para a descentralização? - Nardi, Elton Luiz (Universidade do Vale do Rio do Sinos, 2008)
This thesis analyzes the resource of the decentralization according democratic-participative way, considering it as a political instrument in favor of the democratization of the management of city policies about education. Considering that the choice of this resource is a political option of local governments urging to implement democratic educational projects, this work defends that these projects create local possibilities in relation to the processes that induce to the municipalization, as the ones that inform the Federal Government action, according to the logic of the process of reform of the State. Although recognizing the complexity of the relations that are established in the local scene, considering its social, politics, economic and cultural conditions, it states the role and the capacity of the local power in order to create new experiences, aiming the implementation of a democratic management of city policies about education. According to the empirical research that took place in the city of Concó
Keywords: descentralização; gestão democrática; municipalização; políticas municipais; reforma do Estado; educação; city policies; decentralization; democratic management; municipalization; reform of the State; education; Ciências Humanas